2019
DOI: 10.18415/ijmmu.v6i2.650
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Iraqi Students toward Learning English Language

Abstract: Over learning foreign language process, learners may have different attitudes toward learning the targeted language. These attitudes could accelerate or weaken the acquisition process. Thus, this study conducted to identify whether students have positive or negative attitudes toward learning the English language as well as the study sought to identify if there is a significant difference among study sample in regard of their gender and college. To do this, a sample of (400) non-major English university student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The outcomes of these studies found that students have low attitudes, perspectives and motivation to learn English language. However, they contrast with the results of Pham and Nguyen (2021), Burgos and Molina (2020), Getie (2020), andMutar (2019). These studies found that students have positive attitudes, perspectives, and willingness to learn English language.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The outcomes of these studies found that students have low attitudes, perspectives and motivation to learn English language. However, they contrast with the results of Pham and Nguyen (2021), Burgos and Molina (2020), Getie (2020), andMutar (2019). These studies found that students have positive attitudes, perspectives, and willingness to learn English language.…”
Section: Resultsmentioning
confidence: 59%
“…The results of the study indicated that students' attitudes towards learning EFL were positive. Mutar (2019) investigated Iraqi students' attitudes towards learning English. The questionnaire survey of 400 undergraduates at a non-major English university, that used English as a medium of instruction, revealed that students had positive attitudes towards learning English.…”
Section: Ahmed Et Al (2021) Investigated Iraqi Students' Attitudes To...mentioning
confidence: 99%
“…The research method used for this study is research and development. According to Sugiyono(2012) cited in Subari (2022), research and development is a research method used to produce certain products, and test the effectiveness of these products. This research will produce development products learning media for dialogue journal writing of recount text.…”
Section: Type Of the Researchmentioning
confidence: 99%
“…The previous research on the use of e-module in teaching English yields positive impacts (Y. N. Dewi et al, 2019). Daud et al (2022), for example, clearly demonstrated that the use of e-module is very appealing and easy to use for students to improve their skills in English; effective in improving students' English ability (Subari, 2022); allows students to be more interested and active in receiving the materials (Ruslan & Rauddin, 2022); improves learning outcome (Arosyad et al, 2021); and a learning resource used in this current era (Nurhikmah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%